CYTOTOXIC, ANTIOXIDANT, ANTIMICROBIAL ACTIVITIES OF METHONOL CRUDE EXTRACTS OF CARDIA OBALIQUA (LINN.) - H. U. Khan; R. A. Khan; M. Ahmed (Journal of Animal and Plant Sciences, 2017)
Cardia obaliqua was used traditionally in Pakistan for the treatment of diabetes, microbial infection and jaundice. In the present study we arranged to evaluate the antimicrobial, antioxidant and cytotoxic activities of Cardia obaliqua methanol extract. Cardia obaliqua was obtained from Surrani, District Bannu for preparation of crude methanol extract. A standard protocol of agar well diffusion method was used for characterization of various bacterial strains. Agar dilution method was subjected to investigate the antifungal activities. Death rate of brine shrimps was checked to investigate cytotoxic efficacy of the crude extract. The results showed that the crude extract significantly controlled the microbial growth as compare to control, which was in agreement with the spacious use of tested plant samples in primary healthcare center. Similarly the extract showed significant potency in scavenging of free radicals. From the present study it is inferred that Cardia obaliqua methanol extract was act as a vital role for the detection of new antimicrobial drugs and antioxidant agents; which confirm its conventional uses and its management as beneficial mediator.
Keywords: Cardia obaliqua; Methanolic extract; Cytotoxic activity; Antioxidant activity; Antimicrobial activity